2018
DOI: 10.1111/jam.13758
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution and community composition of anammox bacteria in sediments of a eutrophic shallow lake

Abstract: This is the first study to demonstrate that anammox bacteria displayed the particular distribution in freshwater sediments, which implied a strong response to the anthropogenic eutrophication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
1
2
1
Order By: Relevance
“…Abundance of anammox bacteria based on the hzo gene quantification was positively correlated with the anammox rates, which had a negative correlation with both nosZ I and nosZ II gene abundance (Table ). No significant difference between the hzo gene abundance in the near‐surface and deeper sediments was observed in this study, which differs from the depth profiles of anammox bacterial abundance found in shallow, eutrophic Lake Taihu in China (Qin et al, ). This contrast might be the result of hydrologic control on fluctuating N substrates and dissolved O 2 concentrations in Ashumet Pond, preventing proliferation of anammox bacteria, which have characteristically slow growth rates (Oshiki et al, ).…”
Section: Discussioncontrasting
confidence: 97%
“…Abundance of anammox bacteria based on the hzo gene quantification was positively correlated with the anammox rates, which had a negative correlation with both nosZ I and nosZ II gene abundance (Table ). No significant difference between the hzo gene abundance in the near‐surface and deeper sediments was observed in this study, which differs from the depth profiles of anammox bacterial abundance found in shallow, eutrophic Lake Taihu in China (Qin et al, ). This contrast might be the result of hydrologic control on fluctuating N substrates and dissolved O 2 concentrations in Ashumet Pond, preventing proliferation of anammox bacteria, which have characteristically slow growth rates (Oshiki et al, ).…”
Section: Discussioncontrasting
confidence: 97%
“…3b). This phenomenon was consistent with the decreases of total bacteria abundance with depth in other sediments (Qin et al 2018). These findings further demonstrated that not all anoxic vertical profiles were active denitrification regions.…”
Section: Resultssupporting
confidence: 90%
“…Amplicons were pooled in equimolar amounts and paired-end sequenced on the Illumina MiSeq platform (Illumina) at Majorbio Bio-Pharm Technology Co. Ltd. Raw fastq files were demultiplexed, quality-filtered by Trimmomatic and merged by FLASH according to the criteria, detailed in Qin et al (2018). Operational taxonomic units (OTUs) were clustered based on a 97% identity cut-off using UPARSE (version 7.1 http://drive5.com/upars e/), and chimeric sequences were identified and removed using UCHIME.…”
Section: Microbial Community Structurementioning
confidence: 99%